2003
DOI: 10.1103/physrevb.68.245303
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron resonance of an interacting polaron gas in a quantum well: Magnetoplasmon-phonon mixing

Abstract: Cyclotron-resonance (CR) spectra of a gas of interacting polarons confined in a GaAs/AlAs quantum well are theoretically investigated taking into account the magneto-plasmon-phonon mixing and band nonparabolicity. Contributions of different magneto-plasmon-phonon modes to the total magneto-polaron coupling strength are investigated as a function of the electron density. It is confirmed theoretically, that the resonant magneto-polaron coupling in a high-density GaAs/AlAs quantum well occurs near the GaAs TO-pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Furthermore the 1 − → 2 − transition decays rapidly and the 0 − → 1 − transition only starts to become active in this region making precise analysis difficult. For the moderate doping levels examined here it might be expected that some interactions close to the TO phonon level would also be evident, 27 but this has not been observed. Figure 7 shows the CR energies as a function of magnetic field for the range shown in Fig.…”
Section: Resonant Magnetopolaron Couplingmentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore the 1 − → 2 − transition decays rapidly and the 0 − → 1 − transition only starts to become active in this region making precise analysis difficult. For the moderate doping levels examined here it might be expected that some interactions close to the TO phonon level would also be evident, 27 but this has not been observed. Figure 7 shows the CR energies as a function of magnetic field for the range shown in Fig.…”
Section: Resonant Magnetopolaron Couplingmentioning
confidence: 66%
“…[23][24][25] Initially only a weak interaction was observed, and this was attributed to the PF geometry and the high carrier concentration of the sample ͑1.28ϫ 10 12 cm −2 ͒ screening the polaronic interaction. 26,27 Further studies however have revealed that the RMPC can be enhanced by using a large tilt angle and lower carrier concentrations. 24,25 It was also noted that within the quantum well the LO phonon is no longer a normal mode, as it couples to two-dimensional ͑2D͒ intersubband plasma oscillations ͑plasmons͒ in the 2DEG.…”
Section: Resonant Magnetopolaron Couplingmentioning
confidence: 99%
“…This was already shown in the past, though the experiments reported on bulk semiconductors were restricted to relatively low magnetic fields and focused on a nondegenerate, Maxwellian plasma [18,19]. On the other hand, there exist a number of works, concerning both the Raman scattering [7,20,21] and far-infrared magneto-spectroscopy [22,23] which address the issue of coupling between the electronic and phonon excitations in two-dimensional semiconductor structures [24]. The physics of low energy excitations in these structures is far more complex because of the modification of the energy spectrum due to effects of spatial confinement.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, the situation in quantum wells of III-V semiconductors appears to be different due to the lattice symmetry of these crystals. [4][5][6] If the incident radiation and the magnetic field are orientated perpendicularly to the plane of the 2DEG, there is no CR-LO phonon mixing as the in-plane motion of the electrons and the out-of-plane motion of the lattice cannot couple. Also there is no CR-TO mixing because this phonon does not carry any electric field and the deformation associated with the q = 0 phonon does not allow for the emission or absorption of TO phonons by electrons.…”
Section: Introductionmentioning
confidence: 99%